2022
DOI: 10.1186/s12967-022-03404-9
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000497 and hsa_circ_0000918 contributed to peritoneal metastasis of ovarian cancer via ascites

Abstract: Purpose As a common complication of epithelial ovarian cancer (EOC), malignant ascites contributes to the peritoneal metastasis of EOC. CircRNAs play essential roles in tumor metastasis. However, no circRNAs have been reported to be involved in EOC peritoneal metastasis via ascites. Methods Total of 22 samples from 9 EOC patients containing primary lesions (T), tumor cells from ascites (ASC), and metastatic lesions (M) were included for RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Among the 10 identified DEcircRNAs, hsacirccirc0001947, Circcirc0058058 and hsacirc0004277 have been found to be correlated with AML. [15][16][17][18] Existing research has suggested that hsacirc0001947 inhibits AML cell proliferation via the hsa-miR-329-5p/CREBRF axis. 15 Circ0058058 knockdown accelerated leukocytes apoptosis and inhibited AML progression by targeting miR-4319 to down-regulated EIF5A2 expression, and circ0058058 was considered a possible therapeutic target for AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 10 identified DEcircRNAs, hsacirccirc0001947, Circcirc0058058 and hsacirc0004277 have been found to be correlated with AML. [15][16][17][18] Existing research has suggested that hsacirc0001947 inhibits AML cell proliferation via the hsa-miR-329-5p/CREBRF axis. 15 Circ0058058 knockdown accelerated leukocytes apoptosis and inhibited AML progression by targeting miR-4319 to down-regulated EIF5A2 expression, and circ0058058 was considered a possible therapeutic target for AML.…”
Section: Discussionmentioning
confidence: 99%
“…hsacirc0000497 can promote peritoneal metastasis of ovarian cancer by regulating epithelial-mesenchymal transition (EMT) in vitro. 18 The remaining six circRNAs have not been found to be correlated with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed in accordance with the Declaration of Helsinki and was approved by the institutional ethics committee at Shanghai Tenth People’s Hospital. The mRNA expression data of ovarian cancer were obtained from The Cancer Genome Atlas (TCGA) database ( https://portal.gdc.cancer.gov/ ) and our previous study [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomic analyses revealed that the ASCs exhibited mesenchymal phenotypes while the tumor cells from primary and metastatic lesions displayed gene expression patterns of epithelial cells. In vitro studies showed that these two circRNAs promoted migration and invasion, downregulated ZO1 and E-cadherin, and upregulated N-cadherin and vimentin in EOC cells [ 161 ], suggesting that the circRNAs may contribute to EOC metastasis by modulating EMT. However, the therapeutic potential of these circRNAs remains to be evaluated in vivo.…”
Section: Circrnas As Potential Therapeutic Targetsmentioning
confidence: 99%